Glutaraldehyde-Polymerized Hemoglobin: In Search of Improved Performance as Oxygen Carrier in Hemorrhage Models - Anca D. Farcas; Vlad Al Toma; Ioana Roman; Bogdan Sevastre; Florina Scurtu; Radu Silaghi-Dumitrescu (Bioinorganic Chemistry and Applications)
Hemoglobin- (Hb-) based oxygen carriers (HBOC) have for several decades been explored for treatment of hemorrhage. In our previous top-up tests, HBOC with lower in vitro prooxidant reactivity (incorporating a peroxidase or serum albumin to this end) showed a measurable but small improvement of oxidative stress-related parameters. Here, such HBOCs are tested in a hemorrhage set-up; ovine hemoglobin is also tested for the first time in such a setting, based on in vitro data showing its improved performance versus bovine Hb against oxidative and nitrosative stress agents. Indeed, ovine Hb performs better than bovine Hb in terms of survival rates, arterial tension, immunology, and histology. On the other hand, unlike in the top-up models, where the nonheme peroxidase rubrerythrin as well as bovine serum albumin copolymerized with Hb were shown to improve the performance of HBOC, in the present hemorrhage models rubrerythrin fails dramatically as HBOC ingredient (with a distinct immunological reaction), whereas serum albumin appears not feasible if its source is a different species (i.e., bovine serum albumin fares distinctly worse than rat serum albumin, in HBOC transfusions in rats). An effect of the matrix in which the HBOCs are dissolved (PBS versus gelofusine versus plasma) is noted.